Toxic Prey: Lucas Davenport # 34 - Sandford, John, 1944 February 23- (New York : G. P. Putnam's Sons, 2024)
"Lucas Davenport takes on another challenging case in this thrilling new novel from the #1 New York Times bestselling author"--.
new book 2024 spring.
Keywords: Scientists; Communicable diseases; Suspense fiction; Crime; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction